Alessandra Pagliano. Le ore del sole. Geometria e astronomia negli antichi orologi solari romani (diségno, 2019)
The book by Alessandra Pagliano grew out of research for the exhibition “Le ore del Sole” which took place from September 21st 2018 to January 31st 2019 at the Archaeological Museum of Naples (MANN), where twelve Greek-Roman sundial clocks were displayed. The sundial of the Great Hall of this Museum is also described in the book, showing an eighteenth-century astronomical instrument belonging to an uncommon type of camera obscura sundial. (read more)